Peningkatan Keterampilan Menulis Deskripsi dengan Teknik Tanya Jawab Berbantuan Media Gambar Siswa Kelas VIII.3 SMPN 2 Sungayang Kabupaten Tanah Datar - Ayu, Desmike Putri; Atmazaki, Atmazaki; Amir, Amril (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This research is aimed to explain about the process of using asking-answering technique with the help of picture as media in improving writing ability of descriptive text in the third grade students of SMP 2 Sungayang.This research is a Class Action Research and qualitative research (class action research) that involves: (1) action planning (2)action implementing (3) result observation, and (4) reflection. This research is implemented in two cycles, they are cycle 1 and cycle 2. Ctcle 2 is implemented based on evaluation result at cycle 1. Researcher as presenter in the process of learning, whereas as observer and collaborator is an Indonesian Language teacher in the third grade class of SMP 2 Sungayang.The result of the research shows using asking- answering technique with the help of picture as media in teaching writing descriptive text is effective to improve students’ ability in writing descriptive text. From the result of this class action research, it can be taken a conclude that teaching writing descriptive text by using asking-answering with the help of picture as media improve students’ learning result of the third grade students of SMP 2 Sungayang.